(untitled) (Dimensión Empresarial, 2022)
Objective. Evaluate the importance of the variables resilience and gender as determinants of survival in entrepreneurship microprojects, using the Connor-Davidson scale simplified by Campbell-Sills and Stein (CD-RISC10). Method. A research of a quantitative type, correlational scope and cross-sectional design was carried out. CD-RISC10 was applied to a sample of 100 entrepreneurs from the metropolitan area of ​​ San Luis Potosí, Mexico. Descriptive statistics, exploratory factor analysis, correlation analysis, and hypothesis tests were used to analyze the information to determine the difference or equality of means and variances. A nonlinear regression model with qualitative-logit response was also developed. Findings As relevant findings, a statistically significant difference was found between the average values ​​of the resilience scores obtained by the entrepreneurs whose projects worked less than a year compared to those whose projects worked more than a year; and the weight of resilience and gender were estimated as determinants of business survival.